Psychometric evaluation of the shortened version of the Functional Difficulties Questionnaire to assess thoracic physical function. (January 2020) - Katijjahbe, Mohd Ali; Denehy, Linda; Granger, Catherine L; Royse, Alistair; Royse, Colin; Logie, Sarah; Sturgess, Tamica; Md Ali, Nur Ayub; McManus, Margaret; Clarke-Errey, Sandy; El-Ansary, Doa
Objective: The aim of this study was to investigate the psychometric properties of the shortened version of the Functional Difficulties Questionnaire (FDQ). Design: This is a multisite observational study. Setting: The study was conducted in four tertiary care hospitals in Australia. Subjects: A total of225 participants, following cardiac surgery, were involved in the study. Intervention: Participants completed the original 13-item FDQ and other measures of physical function, pain and health-related quality of life. Method: Item reduction was utilized to develop the shortened version. Reliability was evaluated using intraclass correlation coefficients (ICCs), the smallest detectable change and Bland–Altman plots. The validity and responsiveness were evaluated using correlation. Anchor and distribution-based calculation was used to calculate the minimal clinical important difference (MCID). Results: Item reduction resulted in the creation of a 10-item shortened version of the questionnaire (FDQ-s). Within the cohort of cardiac surgery patient, the mean (SD) for the FDQ-s was 38.7 (19.61) at baseline; 15.5 (14.01) at four weeks and 7.9 (12.01) at three months. Validity : excellent internal consistency (Cronbach's α  > 0.90) and fair-to-excellent construct validity (>0.4). Reliability : internal consistency was excellent (Cronbach's α > 0.8). The FDQ-s had excellent test–retest reliability (ICC = 0.89–0.92). Strong responsiveness overtime was demonstrated with large effect sizes (Cohen's d  > 1.0). The MCID of the FDQ-s was calculated between 4 and 10 out of 100 (in cm). Conclusion: The FDQ-s demonstrated robust psychometric properties as a measurement tool of physical function of the thoracic region following cardiac surgery.